Concomitant changes in the environment and small pelagic fish community of the Gulf of Lions. (July 2020) - Feuilloley, Guillaume; Fromentin, Jean-Marc; Stemmann, Lars; Demarcq, Hervé; Estournel, Claude; Saraux, Claire
Highlights: Rhone river nutrients concentrations significantly decreased since 1990. Rhone river inputs are the main driver of Chl- a in the Gulf of Lions shelf area. Changes were observed in the environment and small pelagic fish population in mid 2000s. Small pelagic community and environmental system of the Gulf of Lions presented the same patterns of variation. Abstract: An important decrease in small pelagic fish condition and size has been observed in the most productive ecosystem of the Mediterranean Sea, the Gulf of Lions, since 2008, leading to an important fishery crisis. Previous studies suggested bottom-up control to be the most probable cause for these changes. Here, we investigate whether an environmental change might have caused such a situation. In the absence of zooplankton time series, this study aims at describing temporal changes in key abiotic factors for the planktonic and fish production of the Gulf of Lions, such as SST, meso-scale fronts, wind-induced coastal upwelling, river discharge, water stratification and deep convection and then at understanding potential link on Chl- a concentration as well as small pelagic fish populations. Our results indicate that the environmental conditions have broadly changed in the Gulf of Lion, with a major change in the mid-2000s, affecting the Chla concentration (which showed a regime shift in 2007), but also the SST, the upwelling and frontal activities, the Rhone river discharge (and particularly the N and P nutrients inputs) as well as the deep winter convection. Those changes could have affected the plankton production and consequently the small pelagic fish community that displayed similar patterns of variations as the environmental conditions.